Pharmacological interventions for hidradenitis suppurativa: a protocol for systematic review and network meta-analysis of randomised trials and non-randomised studies - Phichayut Phinyo; Surapon Nochaiwong; Naritthorn Aroonsakul; Lalita Lumkul; Nutcha Jarupanich; Jacek Szepietowski; Mati Chuamanochan (BMJ Open)
Introduction Therapeutic recommendations for hidradenitis suppurativa (HS) have recently shifted towards non-invasive pharmacological options. Recent evidence has shown promising efficacy for specific treatments. However, data regarding the comparative efficacy of these treatments in patients with HS are still limited. Therefore, we plan to conduct a systematic review and network meta-analysis (NMA) to summarise the benefits and harms of different pharmacological interventions for treating people living with HS.Methods and analysis We will search electronic databases, including Medline, Embase, PubMed, Web of Science, Scopus, CINAHL and Cochrane Library beginning from their inception dates with no language restrictions. A grey literature search will be performed to supplement the electronic databases. Both randomised trials and non-randomised studies using validated measurement tools that investigated the benefits and harms of pharmacological interventions among people living with HS will be included. The predefined primary outcomes will include treatment responses that reflect the patient’s perspective and all-cause discontinuation. Screening, selection, extraction, assessment of the risk of bias and analysis of the strength of the evidence will be performed independently by a pair of reviewers. A two-step approach of traditional pairwise and NMA will be performed. Based on a random-effects model, standardised weighted mean differences and ORs with corresponding 95% CIs will be pooled as effect estimates for the continuous and categorical endpoints, respectively. Statistical and methodological heterogeneities will be assessed. Preplanned subgroup analyses and univariate meta-regression will be conducted to quantify the potential sources of heterogeneity. Evidence-based synthesis will be based on the magnitudes of effect size, evidence certainty and the surface under the cumulative ranking curve values.Ethics and dissemination Ethical approval is not required because this study is based on existing published data. These findings will be disseminated through scientific meetings and publications in peer-reviewed journals.PROSPERO registration number CRD42022302795.